2010
DOI: 10.1159/000316970
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Temporal Profiles of Calpain and Caspase-3 Activities in Postnatal Rat Brain following Repeated Propofol Administration

Abstract: Exposure of newborn rats to a variety of anesthetics has been shown to induce apoptotic neurodegeneration in the developing brain. We investigated the effect of the general anesthetic propofol on the brain of 7-day-old (P7) Wistar rats during the peak of synaptic growth. Caspase and calpain protease families most likely participate in neuronal cell death. Our objective was to examine regional and temporal patterns of caspase-3 and calpain activity following repeated propofol administration (20 mg/kg). P7 rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 74 publications
(67 reference statements)
5
39
0
Order By: Relevance
“…P7 rat pups (n = 92) were administered either 2, 4, or 6 bolus injections of 20 mg/kg of propofol intraperitoneally at 1 h intervals in order to achieve either 2-, 4-, or 6-h-long anesthesia (Milanovic et al 2010). The animals were decapitated either immediately after cessation of the exposure times (designated as the 0 h time point), or after the recovery periods that lasted 4, 16 or 24 h following termination of propofol exposure (and are referred to as 4, 16, and 24 h time points, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…P7 rat pups (n = 92) were administered either 2, 4, or 6 bolus injections of 20 mg/kg of propofol intraperitoneally at 1 h intervals in order to achieve either 2-, 4-, or 6-h-long anesthesia (Milanovic et al 2010). The animals were decapitated either immediately after cessation of the exposure times (designated as the 0 h time point), or after the recovery periods that lasted 4, 16 or 24 h following termination of propofol exposure (and are referred to as 4, 16, and 24 h time points, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding our previous findings about propofol anesthesia duration-and structure-dependent neurodegeneration (Milanovic et al 2010), we opted to test long-term behavioral consequences of 6 h-long propofol exposure. Behavioral experiments were performed between 09:00 and 14:00 h. Animals neonatally exposed to propofol anesthesia (n = 6 per group) and control, saline injected animals (n = 6 per group) were habituated to experimental cages for three consecutive days (intersession activity) starting from age P35 (early adolescence in rats, Laviola et al 2003).…”
Section: Behavioral Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health Sciences Maringá, v. 39, n. 2, p. 133-139, July-Dec., 2017 that these receptors were modulated by anesthetics; however, information about the effects of propofol on central neurons is scarce. In addition, propofol causes the death of brain cells in neonatal experimental animal (Vutskits, Gascon, Tassonyi, & Kiss, 2005;Cattano et al, 2008;Pesić et al, 2009;Bercker et al, 2009;Milanovic et al, 2010) and long-term behavioral deficits in the developing brain (Yu, Jiang, Gao, Liu, & Chen, 2013). Another example of propofol toxicity was verified by Cheng et al, (2010) who found that propofol prevented the proliferation of cardiac fibroblasts, by interfering with the generation of reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%